GOVERNMENT DOMINATION IN ANTARA TV THE FEATURE NEWS PRODUCTION PROCESS OF â€œMATA INDONESIAâ€ - Abdul Kholik (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2020)
The Ministry of Communication and Informatics has the task to distribute information on the various state activities, social and other community activities. The task of producing and disseminating this information is given to a Public Company of National News Agency (LKBN / Lembaga Kantor Berita Nasional) Antara. The research was carried out with a qualitative approach with the research of the feature news Antara TV, Mata Indonesia as an object. The study was conducted by performing a direct observations on the production process of the feature news Mata Indonesia. In the Mata Indonesia production process the Ministry has a dominant role in determining the direction and policy of Mata Indonesia. With economic and political power, the Ministry has intervened since the production designs, production processes in the field and regulate the final output of Mata Indonesia. To still be able to produce Mata Indonesia, the editor of Antara TV applies the gatekeeper function. Where all elements involved in selecting information will be presented. Keywords: media political economy, gatekeeper, journalistic tv, feature news